Scout analysis of soccer: new look on the Brazilian championship - Saraiva Flores, F.; Gassen Balsan, L. A. (International Journal of Sports Science, 2016)
The aim of this study is to analyze the average performances of the teams that participated in the Brazilian Soccer Championship using the Scout Method, trying to correlate the patterns with and the final rankings. In order to achieve the results, 380 matches of the Brazilian Soccer Championship, season 2012, were analyzed. The findings of this study show that the highest proportion of goals are scored in the second half. G1 obtained more home and away wins and less home and away defeats, in comparison to the others three groups. In addition, G1 presented more scored goals and less wrong passes than the other groups. The findings showed positive correlations between the total points with victories, goals and goals difference. In addition, negative correlations could be found between the total points and losses with goals against. The results from this study raise the relevance of using technical variables to understand the final ranking in a soccer championship.